Crossing African Borders - Cristina Udelsmann Rodrigues, Jordi Tomàs (dir.) (Centro de Estudos Internacionais, 2012)
This publication is one of the results of a conference organised in Lisbon in 2011 on the theme of African borders and their relationships with migration and mobility. The selected papers are a sample of the diverse perspectives on the general theme presented at the meeting. The African Borderlands Research Network (ABORNE) promoted this event, allowing a substantial number of its members to exchange results of ongoing and long-term research. The Fundação para a Ciência e a Tecnologia (Portug...